Olfactometric diagnosis of lung cancer by canine scent – A double-blinded study. (March 2022) - Riedlova, Petra; Tavandzis, Spiros; Kana, Josef; Tobiasova, Miroslava; Jasickova, Iva; Roubec, Jaromir
Abstract: Background: Lung cancer is one of the most often diagnosed tumours in the world with the highest mortality. A major problem and reason for the high mortality from lung cancer is its diagnosis in the late stages. The main goal of preventing lung cancer deaths is early detection in the early stages and accurate diagnosis, which must be followed by targeted treatment. Nevertheless, even top diagnostic techniques do not have the same accuracy and sensitivity as a dog's sense of smell. Methods: The study aims to present the results of olfactometric detection of lung cancer using the smell of dogs in unblinded, single-blinded and double-blinded studies. 115 serum samples or breath from patients with lung cancer and 101 samples from healthy people were used for the training. The group consisted of women and men of Indo-European origin, mostly from the Moravian-Silesian region in Czech Republic. Two dogs were selected for the study. Results: In the case of tumor detection in the form of unblinded tests, Bugs had a sensitivity of 91% and a specificity of 92%. Boolomo had a sensitivity of 89% and a specificity of 81%. For single-blinded tests, Bugs had a sensitivity of 71%. The sensitivity of Boolomo was set at 90%. After meeting the sensitivity limit of 70%, dogs were included in the double-blinded studies. The highest accuracy was set at 68% for Bugs, 83% for Boolomo. Conclusion: When a tumour is diagnosed in the late stages, it is a great burden on both the health and economic systems of the state. Unfortunately, there is still no suitable screening test to detect the tumour at an early stage, so any other method of detection seems desirable. Trained dogs are used in many fields, why not also in medicine and the diagnosis of tumours? Highlights: A major problem and reason for the high mortality from lung cancer is its diagnosis in the late stages. Modern diagnostics is still not able to detect patients with lung cancer at an early stage. The main goal of preventing lung cancer deaths is early detection in the early stages of the disease and accurate diagnosis, which must be followed by targeted treatment. There are no warning signs of the very early stages of the disease that would force the patient to see a doctor in time.